KERATOCONUS (Journal of Pharmaceutical Negative Results, 2023)
Keratoconus is a progressive noninflammatory ectatic disease of the cornea with onset at puberty in most cases. Both genetic and nongenetic or environmental factors have been implicated. Keratoconus has been associated with numerous genetic systemic disorders. many keratoconus-associated syndromes have a high incidence of eczema and atopy, such as Down syndrome, hyper-IgE syndrome, ichthyosis, and oculodentodigital syndrome, Turner syndrome (conjunctival lymphangiectasia), autographism and Mulvihill–Smith syndrome. In each of these syndromes associated with atopy and eczema, associations are known to include both keratoconus and eye rubbing. Keratocyte density, possibly from IL-1–induced apoptosis, is reduced in keratoconus and can be demonstrated as well with eye rubbing and with contact lens wear. A recently developed treatment for keratoconus is corneal collagen crosslinking (CXL). In CXL, stromal fibers are photopolymerized by the combined action of a photosensitizing substance (riboflavin or vitamin B2) and ultraviolet rays A.